2010
DOI: 10.2174/1876823701002010043
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms Linking Adiponectin Receptor Signalling and Cancer

Abstract: Abstract:Adiponectin is an adipose tissue-derived hormone. It is a key hormone that is responsible for insulin sensitization, and its circulating level is inversely associated with abdominal obesity. Recent studies have shown that a reduced plasma adiponectin level is significantly correlated with the risk of various kinds of cancers. Adiponectin may influence the cancer risk by modulating the metabolic environment indirectly. However several cancer cells express adiponectin receptors, suggesting that adiponec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…Coffee consumption has been shown to be associated with higher adiponectin plasma levels [2][3][4]6], an endogenous insulin sensitizer [8]. Higher adiponectin plasma levels lead in turn to decreased concentrations of both plasma insulin and IGF-1 [5]. Insulin levels have been observed to be directly associated with PCa-specific mortality in two prospective studies [34,35], although no association has been observed with total PCa incidence in a case-control study [36].…”
Section: Annals Of Oncology Original Articlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Coffee consumption has been shown to be associated with higher adiponectin plasma levels [2][3][4]6], an endogenous insulin sensitizer [8]. Higher adiponectin plasma levels lead in turn to decreased concentrations of both plasma insulin and IGF-1 [5]. Insulin levels have been observed to be directly associated with PCa-specific mortality in two prospective studies [34,35], although no association has been observed with total PCa incidence in a case-control study [36].…”
Section: Annals Of Oncology Original Articlesmentioning
confidence: 99%
“…introduction Coffee, the most common beverage in the Western world excluding water [1], has been observed to reduce the concentrations of both plasma insulin and insulin-like growth factor 1 levels (IGF-1) through increased levels of adiponectin [2][3][4][5][6], an endogenous insulin sensitizer which is inversely associated with obesity [7][8][9]. Coffee has also been observed to be associated with increased sex hormone-binding globulin (SHBG) concentrations [10,11] and reduced oxidative stress [12][13][14].…”
mentioning
confidence: 99%
“…Both FASN and AdipoR2 play key roles in fatty acid and lipid metabolism, and both have close relationships with insulin; insulin increases expression of FASN in adipocytes, whereas AdipoR2 expression has been shown to be associated with insulin sensitivity (43). Further, overexpression of the adiponectin receptors in animal studies have demonstrated their ability to stimulate fatty acid oxidation via activation of peroxisome proliferator-activated receptor and adenosine monophosphate-activated protein kinase (44,45), whereas FASN is thought to be inversely related to adenosine monophosphate-activated protein kinase activation. These inconsistencies again point to a complex causal pathway and add further evidence for the important role of insulin and lipid metabolism in prostate cancer.…”
Section: Discussionmentioning
confidence: 99%